Intestinal Mucosal Barrier Is Regulated by Intestinal Tract Neuro-Immune Interplay - You, Xin-yu; Zhang, Han-yu; Han, Xu; Wang, Fang; Zhuang, Peng-wei; Zhang, Yan-jun (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD), irritable bowel syndrome (IBS) and severe central nervous system (CNS) injury can lead to intestinal mucosal barrier damage, which can cause endotoxin/enterobacteria translocation to induce infection and is closely related to the progression of metabolic diseases, cardiovascular and cerebrovascular diseases, tumors and other diseases. Hence, repairing the intestinal barrier represents a potential therapeutic target for many diseases. Enteral afferent nerves, efferent nerves and the intrinsic enteric nervous system (ENS) play key roles in regulating intestinal physiological homeostasis and coping with acute stress. Furthermore, innervation actively regulates immunity and induces inherent and adaptive immune responses through complex processes, such as secreting neurotransmitters and hormones and regulating their corresponding receptors. In addition, intestinal microorganisms and their metabolites play a regulatory role in the intestinal mucosal barrier. This paper primarily discusses the interactions between norepinephrine (NE) and β-adrenergic receptors, cholinergic anti-inflammatory pathways (CAIPs), nociceptive receptors, complex intestinal neural networks, gut microbes and various immune cells with their secreted cytokines to summarize their key roles in regulating intestinal inflammation and improving mucosal barrier function.